50 years of the International Committee on Taxonomy of Viruses: progress and prospects. - Adams, M; Lefkowitz, E; King, A; Harrach, B; Harrison, R; Knowles, N; Kropinski, A; Krupovic, M; Kuhn, J; Mushegian, A; Nibert, M; Sabanadzovic, S; et al. (Springer, 2017)
To mark the 50th anniversary of the origins of the International Committee on Taxonomy of Viruses (ICTV), we present a brief history of the foundation, consolidation, establishment and growth of this organisation. We also outline recent developments, supported by a grant from the Wellcome Trust, that has facilitated a dialogue with the virology community that will lead to substantial changes to the operations and public contributions of ICTV. These developments aim to generate improved open access resources, including a freely available and regularly updated online ICTV Report. Bioresource funding will also enable a series of meetings between the ICTV and the broader community to focus on major challenges facing virus taxonomy, with discussion outcomes from such workshops used to inform future ICTV policy and practice.